Heterogeneous structure molybdenum alloy and preparation method thereof

By mixing MoO3 powder with carbon powder, and through sintering, dry mixing and molding, an isomeric structured molybdenum alloy is formed, which solves the problem of high cost of the existing process, realizes high strength and high ductility of the material, and reduces the preparation cost.

CN119530591APending Publication Date: 2025-02-28XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411721297.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing isomeric structure molybdenum alloy preparation process is costly and it is difficult to meet the strict requirements of modern technology for material performance.

Method used

The isomeric structure molybdenum alloy is formed by mixing MoO3 powder with carbon powder, and sintering, dry mixing and molding. This method generates the Mo2C enhanced phase in situ, pins the grain boundaries, refines the grains, improves density, and reduces costs.

Benefits of technology

It has achieved low production cost of isomeric structure molybdenum alloys, and the material has good yield strength and elongation, which can meet the needs of modern technology for material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530591A_ABST
    Figure CN119530591A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a molybdenum alloy with a heterogeneous structure and the molybdenum alloy with the heterogeneous structure, and relates to the technical field of powder metallurgy. The preparation method comprises the following steps: mixing MoO3 powder with carbon powder to obtain carbon-coated MoO3 powder; the carbon-coated MoO3 powder is sintered in an inert gas atmosphere, so that first mixed powder is obtained, and the first mixed powder comprises Mo2C powder and molybdenum powder; performing dry mixing on the first mixed powder to obtain second mixed powder; and carrying out mold pressing on the second mixed powder to obtain a blank, and sintering the blank in a hydrogen atmosphere to obtain the molybdenum alloy with the heterogeneous structure. The preparation cost of the molybdenum alloy with the heterogeneous structure can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of powder metallurgy, and in particular to a preparation method of a heterogeneous molybdenum alloy and a heterogeneous molybdenum alloy. Background Art

[0002] Molybdenum (Mo) has the characteristics of high melting point, high high temperature strength, small expansion coefficient, good thermal and electrical conductivity, and strong corrosion resistance. Molybdenum and its alloys have been widely used in military, aviation, electronics and other fields. However, with the rapid development of modern science and technology, the requirements for material properties in various fields are becoming increasingly stringent, and the mechanical properties of molybdenum alloys cannot meet the requirements.

[0003] In order to improve the mechanical properties, molybdenum alloys with heterogeneous structures have emerged. However, the current solutions for preparing molybdenum alloys with heterogeneous structures generally have the problem of high cost.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] The purpose of the present disclosure is to provide a method for preparing a heterogeneous molybdenum alloy and a heterogeneous molybdenum alloy, thereby overcoming the problem of high preparation cost of heterogeneous molybdenum alloys at least to a certain extent.

[0006] According to a first aspect of the present disclosure, a method for preparing a heterogeneous molybdenum alloy is provided, comprising: 3 The powder is mixed with carbon powder to obtain carbon-coated MoO 3 Powder; Carbon coated with MoO in an inert gas atmosphere 3 The powder is sintered to obtain a first mixed powder, the first mixed powder comprising Mo 2 C powder and molybdenum powder; dry-mixing the first mixed powder to obtain a second mixed powder; molding the second mixed powder to obtain a blank, and sintering the blank in a hydrogen atmosphere to obtain a heterogeneous molybdenum alloy.

[0007] Optionally, MoO 3 The powder is mixed with carbon powder to obtain carbon-coated MoO 3 Powder, comprising: MoO 3 The powder is mixed with carbon powder and dried to obtain carbon-coated MoO 3 powder.

[0008] Alternatively, for the preparation of carbon-coated MoO 3In the powder process, the ball-to-material ratio is 3:1 to 7:1, the rotation speed is 350r / min to 550r / min, and the ball milling mixing time is 10h to 15h.

[0009] Optionally, MoO 3 The mass ratio of powder to carbon powder is 4:1 to 6:1, MoO 3 The particle size of the powder is 2 μm to 4 μm, and the particle size of the carbon powder is 10 nm to 30 nm.

[0010] Alternatively, carbon-coated MoO 3 The powder is sintered to obtain a first mixed powder, comprising: sintering the carbon-coated MoO at a temperature of 900°C to 1300°C in an inert gas atmosphere; 3 The powder is sintered to obtain a first mixed powder.

[0011] Optionally, the second mixed powder is molded to obtain a blank, including: using a tablet press to mold the second mixed powder to obtain a green blank; using a cold isostatic press to press the green blank to obtain the blank.

[0012] Optionally, the tablet press has a pressure of 150 MPa to 200 MPa, and a holding time of 5 min to 10 min.

[0013] Optionally, the pressure of the cold isostatic press is 200 MPa to 300 MPa, and the holding time is 5 min to 10 min.

[0014] Optionally, the blank is sintered in a hydrogen atmosphere to obtain a heterogeneous molybdenum alloy, including: sintering the blank at a temperature of 1300° C. to 1600° C. in a hydrogen atmosphere for 1 h to 4 h to obtain a heterogeneous molybdenum alloy.

[0015] According to a second aspect of the present disclosure, a heterogeneous structure molybdenum alloy is provided, which is prepared by any of the above-mentioned methods for preparing heterogeneous structure molybdenum alloys.

[0016] In the scheme of the exemplary embodiment of the present disclosure, on the one hand, a molybdenum alloy with a heterogeneous structure is prepared by material mixing, sintering, pressing, etc., and the process is simple, easy to implement, and the preparation cost is low. On the other hand, Mo is generated in situ in the Mo alloy. 2 The C reinforcement phase plays a role in pinning the grain boundaries during the sintering process of the molybdenum alloy, reducing the porosity of the molybdenum alloy and achieving the effect of improving the density. On the other hand, the present disclosure adopts a dry mixing method to break up the agglomerated materials and ensure that the Mo powder and Mo 2 C is mixed evenly to avoid stratification due to different material densities. On the other hand, the heterogeneous structure molybdenum alloy obtained in the present disclosure comprises a multi-level scale reinforcement phase and multi-scale molybdenum grains, and can have good yield strength and elongation.

[0017] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0019] Figure 1 A flow chart of a method for preparing a heterogeneous structure molybdenum alloy according to an exemplary embodiment of the present disclosure is schematically shown.

[0020] Figure 2 A scanning electron microscope (SEM) image of the fracture of the aluminum alloy prepared in Example 1 of the present disclosure is shown.

[0021] Figure 3 The SEM image of the fracture of the aluminum alloy prepared in Example 2 of the present disclosure is shown.

[0022] Figure 4 The SEM images of the aluminum alloy fracture prepared in Example 3 of the present disclosure are shown. Among them, (a) is a SEM image at a scale of 20 μm; (b) is a SEM image at a scale of 10 μm; (c) is a SEM image at a scale of 5 μm.

[0023] Figure 5 The SEM image of the fracture of the aluminum alloy prepared in Example 4 of the present disclosure is shown.

[0024] Figure 6 The SEM image of the fracture of the aluminum alloy prepared in Example 5 of the present disclosure is shown.

[0025] Figure 7 The SEM image of the fracture surface of the pure molybdenum alloy of Comparative Example 1 of the present disclosure is shown.

[0026] Figure 8 The yield strength curves of the molybdenum alloys prepared in Examples 1 to 5 and Comparative Example 1 of the present disclosure are shown. DETAILED DESCRIPTION

[0027] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, processes, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0028] In addition, the accompanying drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated descriptions will be omitted. The flowcharts shown in the accompanying drawings are only exemplary illustrations and do not necessarily include all the steps. For example, some steps can also be decomposed, while some steps can be combined or partially combined, so the actual execution order may change according to actual conditions. In addition, all the terms "first", "second", etc. below are only for the purpose of distinction and should not be used as limitations of the present disclosure.

[0029] Means to improve the strength and plasticity of molybdenum alloys can include grain refinement or the introduction of reinforcing phases. By adding second-phase particles, the movement of molybdenum grain boundaries is pinned to refine the grains of molybdenum alloys. The more second-phase particles are added, the smaller the size, the more uniform the distribution, and the smaller the grain size of the molybdenum alloy. However, when too many second-phase particles are added, they tend to agglomerate and be unevenly distributed, thereby weakening the grain refinement effect and reducing strength and toughness.

[0030] The Hall-Petch principle shows that the strength of a material increases as the grain size decreases within a certain range, but the dislocations that can be accommodated in fine grains are limited, which is specifically manifested as poor strain hardening ability. Introducing an appropriate amount of coarse grains into fine-grained materials can provide a larger space for newly generated dislocations, thereby improving the strain hardening ability of the material. Heterogeneous materials are composed of microstructure units with significant strength differences, and the regional size of the structural unit can vary from micrometers to millimeters. During the deformation of the material, a large strain gradient is generated near the interface of the structural unit, resulting in back stress and back stress work hardening, and small grains will synergistically strengthen with large grains. The texture strengthening of coarse grains and the grain boundary strengthening of fine grains synergistically improve the tensile yield strength and ultimate tensile strength of the alloy, achieving a simultaneous improvement in material strength and ductility. Compared with homogeneous materials, heterogeneous metal materials have better mechanical properties, which can make metal materials have both high strength and high plasticity.

[0031] At present, there are three preparation processes for heterogeneous alloys: The first is to combine plastic deformation treatments such as extrusion and rolling of metal materials with heat treatments such as annealing and aging to prepare heterogeneous metal materials. The second is to use surface treatment technologies such as thermal spraying, magnetron sputtering, laser cladding, or powder metallurgy technologies such as plasma sintering to prepare heterogeneous metal coatings or metal sheets. The third is to design special processes for heterogeneous metal materials, such as powder thixoforming and bimodal milling.

[0032] Although the above-mentioned heterogeneous alloy preparation processes can achieve the simultaneous improvement of the strength and plasticity of metal materials, the processing requirements are high and the preparation cycle is long, which increases the cost of heterogeneous alloys and makes it difficult to control the formation process of heterogeneous structures.

[0033] In order to solve or at least alleviate the above problems, the embodiments of the present disclosure provide a novel method for preparing a heterogeneous molybdenum alloy.

[0034] Figure 1 The flowchart of the method for preparing a heterogeneous structure molybdenum alloy according to an exemplary embodiment of the present disclosure is schematically shown. Figure 1 The method for preparing the heterogeneous structure molybdenum alloy according to the embodiment of the present disclosure may include the following steps:

[0035] S12.MoO 3 The powder is mixed with carbon powder to obtain carbon-coated MoO 3 powder.

[0036] In an exemplary embodiment of the present disclosure, MoO 3 The mass ratio of powder to carbon powder is 4:1 to 6:1. 3 The particle size of the powder is 2 μm to 4 μm. The particle size of the carbon powder is 10 nm to 30 nm, and the BET specific surface area of ​​the carbon powder can be greater than 80 m 2 , specifically, it can be 90m 2 Up to 110m 2 .

[0037] MoO can be wet-mixed by ball milling. 3 The powder is mixed with carbon powder to obtain carbon-coated MoO 3 Specifically, in this process, the solvent can be deionized water or ethanol, the ball-to-material ratio is 3:1 to 7:1, the rotation speed is 350 r / min to 550 r / min, and the ball milling mixing time is 10 h to 15 h.

[0038] The nano-scale carbon powder used in the present invention can not only be used as MoO 3 The reducing agent MoO 3 Reduced to Mo, it can also be used as Mo2 C nucleation site, carbonizing the reduced Mo powder into Mo 2 C. The ball milling process effectively improved the carbon in MoO 3 The distribution in the 2 C is smaller in size and more evenly distributed in the matrix, making the reinforcing phase Mo 2 C plays a greater role in pinning grain boundaries and refining grains.

[0039] S14. Carbon-coated MoO in an inert gas atmosphere 3 The powder is sintered to obtain a first mixed powder, the first mixed powder comprising Mo 2 C powder and molybdenum powder.

[0040] Specifically, the carbon-coated MoO 3 The powder is sintered to obtain a first mixed powder.

[0041] Nano-scale carbon particles are smaller, have greater storage energy, and have a greater tendency to transform to a low-energy state. After adding nano-carbon powder, the total surface energy of the alloy powder is larger, sintering is easier, and the lattice distortion in the particles will also release energy during the sintering process. Therefore, when other conditions are constant, the finer the powder, the higher the defect content in the crystal structure, the greater the sintering shrinkage, and the higher the density, which is conducive to sintering densification.

[0042] S16. Dry-mixing the first mixed powder to obtain a second mixed powder.

[0043] According to some embodiments of the present disclosure, dry mixing can be achieved by stirring or ball milling, and the present disclosure does not limit the dry mixing method and time. It should be noted that no solvent is added during the dry mixing process.

[0044] Through the dry mixing process, the agglomerated materials can be broken up to ensure that the Mo powder and Mo 2 C Mix evenly to avoid stratification due to different material densities.

[0045] S18. The second mixed powder is molded to obtain a blank, and the blank is sintered in a hydrogen atmosphere to obtain a heterogeneous molybdenum alloy.

[0046] According to some embodiments of the present disclosure, first, the second mixed powder can be molded using a tablet press to obtain a green compact. Specifically, the tablet press has a pressure of 150 MPa to 200 MPa and a holding time of 5 min to 10 min.

[0047] Next, the green body can be pressed by a cold isostatic press to obtain a blank. Specifically, the pressure of the cold isostatic press is 200 MPa to 300 MPa, and the holding time is 5 min to 10 min.

[0048] After the ingot is obtained, the ingot may be sintered at 1300° C. to 1600° C. in a hydrogen atmosphere for 1 h to 4 h to obtain a molybdenum alloy with a heterogeneous structure.

[0049] In the sintering process, sintering necks are first formed between molybdenum particles at high temperature, and the interface of molybdenum particles forms grain boundaries and moves into the interior of the particles. During the grain growth process, when the grain boundary movement speed is large, the pore migration or pore disappearance is slower than the grain boundary movement. The grain boundary and pore are separated, which will cause the pores to remain in isolation inside the grains and are difficult to disappear. 2 As the second phase particles, C plays the role of pinning the grain boundaries, hindering the movement of the grain boundaries during the sintering process of the alloy, causing the pores to diffuse along the grain boundaries to both ends and disappear outside the alloy, thereby improving the density of the alloy.

[0050] The present invention adopts a mixed material process of wet grinding and dry mixing, and constructs a fine-grained heterogeneous mixed structure required for a strong and tough molybdenum alloy through powder ball milling, reduction, dispersion of reinforcing phases, and press sintering, which promotes the texture strengthening of coarse grains and the grain boundary strengthening of fine grains, synergistically improves the tensile yield strength and ultimate tensile strength of the alloy, and achieves a simultaneous improvement in the strength and ductility of the molybdenum alloy. The room temperature yield strength of the heterogeneous structure molybdenum alloy can reach 1198MPa, and the elongation can reach 37%.

[0051] The above-mentioned preparation process of the present disclosure is described below through examples.

[0052] Example 1

[0053] First, MoO 3 The powder was mixed with carbon powder by ball milling, with a ball-to-material ratio of 4:1 and a ball milling speed of 350 r / min for 10 h, and then dried to obtain carbon-coated MoO 3 powder.

[0054] Next, the carbon was coated with MoO at 900 °C. 3 The powder was placed in an argon atmosphere and sintered for 1 hour to obtain a first mixed powder. The first mixed powder was subjected to dry mixing and dispersion mixing to make the in-situ generated Mo 2 C is uniformly dispersed in the molybdenum powder to obtain a second mixed powder.

[0055] Subsequently, the second mixed powder was molded at a pressure of 150 MPa with a holding time of 5 minutes. After the molding, the green body was placed in a cold isostatic press for pressing at a pressure of 200 MPa with a holding time of 5 minutes to obtain a green body.

[0056] Then, the blank is sintered in a hydrogen atmosphere at a sintering temperature of 1400° C. for 1 hour to obtain a heterogeneous molybdenum alloy. Figure 2 The SEM image of the fracture of the aluminum alloy prepared in Example 1 of the present disclosure is shown.

[0057] Example 2

[0058] First, MoO 3 The powder was mixed with carbon powder by ball milling, with a ball-to-material ratio of 4:1 and a ball milling speed of 370 r / min for 12 h, and then dried to obtain carbon-coated MoO 3 powder.

[0059] Next, the carbon was coated with MoO at 1000°C. 3 The powder was placed in an argon atmosphere and sintered for 1 hour to obtain a first mixed powder. The first mixed powder was subjected to dry mixing and dispersion mixing to make the in-situ generated Mo 2 C is uniformly dispersed in the molybdenum powder to obtain a second mixed powder.

[0060] Subsequently, the second mixed powder was molded at a pressure of 170 MPa with a holding time of 5 minutes. After molding, the green body was placed in a cold isostatic press for pressing at a pressure of 220 MPa with a holding time of 5 minutes to obtain a green body.

[0061] Then, the blank is sintered in a hydrogen atmosphere at a sintering temperature of 1400° C. for 2 hours to obtain a heterogeneous molybdenum alloy. Figure 3 The SEM image of the fracture of the aluminum alloy prepared in Example 2 of the present disclosure is shown.

[0062] Example 3

[0063] First, MoO 3 The powder was mixed with carbon powder by ball milling, with a ball-to-material ratio of 5:1 and a ball milling speed of 400 r / min for 13 h, and then dried to obtain carbon-coated MoO 3 powder.

[0064] Next, the carbon was coated with MoO at 1010°C. 3 The powder was placed in an argon atmosphere and sintered for 1 hour to obtain a first mixed powder. The first mixed powder was subjected to dry mixing and dispersion mixing to make the in-situ generated Mo 2 C is uniformly dispersed in the molybdenum powder to obtain a second mixed powder.

[0065] Subsequently, the second mixed powder was molded at a pressure of 180 MPa with a holding time of 5 minutes. After molding, the green body was placed in a cold isostatic press for pressing at a pressure of 240 MPa with a holding time of 5 minutes to obtain a green body.

[0066] Then, the blank is sintered in a hydrogen atmosphere at a sintering temperature of 1400° C. for 2 hours to obtain a heterogeneous molybdenum alloy. Figure 4 The SEM image of the fracture of the aluminum alloy prepared in Example 3 of the present disclosure is shown.

[0067] Example 4

[0068] First, MoO 3 The powder was mixed with carbon powder by ball milling, with a ball-to-material ratio of 5:1 and a ball milling speed of 450 r / min for 14 h, and then dried to obtain carbon-coated MoO 3 powder.

[0069] Next, the carbon was coated with MoO at 1020°C. 3 The powder was placed in an argon atmosphere and sintered for 1 hour to obtain a first mixed powder. The first mixed powder was subjected to dry mixing and dispersion mixing to make the in-situ generated Mo 2 C is uniformly dispersed in the molybdenum powder to obtain a second mixed powder.

[0070] Subsequently, the second mixed powder was molded at a pressure of 190 MPa with a holding time of 5 minutes. After molding, the green body was placed in a cold isostatic press for pressing at a pressure of 260 MPa with a holding time of 5 minutes to obtain a green body.

[0071] Then, the blank is sintered in a hydrogen atmosphere at a sintering temperature of 1400° C. for 2 hours to obtain a heterogeneous molybdenum alloy. Figure 5 The SEM image of the fracture of the aluminum alloy prepared in Example 4 of the present disclosure is shown.

[0072] Example 5

[0073] First, MoO 3 The powder was mixed with carbon powder by ball milling, with a ball-to-material ratio of 5:1 and a ball milling speed of 500 r / min for 15 h, and then dried to obtain carbon-coated MoO 3 powder.

[0074] Next, the carbon was coated with MoO at 1030 °C. 3 The powder was placed in an argon atmosphere and sintered for 1 hour to obtain a first mixed powder. The first mixed powder was subjected to dry mixing and dispersion mixing to make the in-situ generated Mo 2 C is uniformly dispersed in the molybdenum powder to obtain a second mixed powder.

[0075] Subsequently, the second mixed powder was molded at a pressure of 200 MPa with a holding time of 5 minutes. After molding, the green body was placed in a cold isostatic press for pressing at a pressure of 300 MPa with a holding time of 5 minutes to obtain a green body.

[0076] Then, the blank is sintered in a hydrogen atmosphere at a sintering temperature of 1400° C. for 2 hours to obtain a heterogeneous molybdenum alloy. Figure 6 The SEM image of the fracture of the aluminum alloy prepared in Example 5 of the present disclosure is shown.

[0077] Comparative Example 1

[0078] The molybdenum powder was molded at 200 MPa for 5 minutes, and the green body was placed in a cold isostatic press for pressing at a pressure of 300 MPa for 5 minutes. The green body was then sintered in a hydrogen atmosphere at a sintering temperature of 1400°C for 2 hours to prepare a molybdenum alloy. Figure 7 The SEM image of the fracture surface of the pure molybdenum alloy of Comparative Example 1 of the present disclosure is shown.

[0079] For the molybdenum alloys prepared in Examples 1 to 5 and Comparative Example 1, a Vickers hardness tester was used to test the hardness of the molybdenum alloys, and a room temperature compression test was performed to obtain the micro Vickers hardness and the room temperature compressive yield strength, respectively. Figure 8 The yield strength curves of the molybdenum alloys prepared in Examples 1 to 5 of the present disclosure and Comparative Example 1 are shown. The specific results are shown in Table 1, wherein Comparative Example 1 corresponds to pure molybdenum.

[0080] Table 1

[0081]

[0082] From Table 1 and Figures 2 to 7 It can be seen that the grain size of the molybdenum alloy prepared by the embodiments of the present disclosure is different from the grain size of the pure molybdenum alloy, and the grain size of the pure molybdenum alloy is about 8μm. After carbon addition, wet grinding, in-situ reduction, dry mixing, and pressing and sintering, the grain size of the molybdenum alloy has changed significantly. The grain size of the molybdenum alloy samples of Examples 1 to 5 becomes finer with the increase of carbon content. The fracture of Example 3 shows obvious heterogeneous characteristics, and grains of 8mm and 3mm in size are evenly distributed in the molybdenum alloy. Moreover, the yield strength of the molybdenum alloy of Example 3 can reach 1198MPa, and the elongation can also reach 37%.

[0083] Furthermore, the embodiments of the present disclosure also provide a heterogeneous structure molybdenum alloy, which is prepared by the above-mentioned preparation method of the heterogeneous structure molybdenum alloy.

[0084] It should be noted that although the steps of the method in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.

[0085] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0086] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the true scope and spirit of the present disclosure are indicated by the claims.

[0087] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A method for preparing a heterogeneous molybdenum alloy, characterized in that: include: Mixing MoO3 powder with carbon powder to obtain carbon-coated MoO3 powder; Sintering the carbon-coated MoO3 powder in an inert gas atmosphere to obtain a first mixed powder, wherein the first mixed powder includes Mo2C powder and molybdenum powder; dry-mixing the first mixed powder to obtain a second mixed powder; The second mixed powder is molded to obtain a blank, and the blank is sintered in a hydrogen atmosphere to obtain a heterogeneous structure molybdenum alloy.

2. The preparation method according to claim 1, characterized in that: MoO3 powder is mixed with carbon powder to obtain carbon-coated MoO3 powder, comprising: The MoO3 powder and the carbon powder are mixed by ball milling wet mixing, and the carbon-coated MoO3 powder is obtained after drying.

3. The preparation method according to claim 2, characterized in that: In the process of preparing the carbon-coated MoO3 powder, the ball-to-material ratio is 3:1 to 7:1, the rotation speed is 350 r / min to 550 r / min, and the ball milling mixing time is 10 h to 15 h.

4. The preparation method according to any one of claims 1 to 3, characterized in that The mass ratio of the MoO3 powder to the carbon powder is 4:1 to 6:1, the particle size of the MoO3 powder is 2 μm to 4 μm, and the particle size of the carbon powder is 10 nm to 30 nm.

5. The preparation method according to claim 1, characterized in that: The carbon-coated MoO3 powder is sintered in an inert gas atmosphere to obtain a first mixed powder, comprising: The carbon-coated MoO3 powder is sintered at a temperature of 900° C. to 1300° C. in an inert gas atmosphere to obtain a first mixed powder.

6. The preparation method according to claim 1, characterized in that: The second mixed powder is molded to obtain a blank, comprising: Using a tablet press to press the second mixed powder to obtain a green compact; The green body is pressed by a cold isostatic press to obtain a blank.

7. The preparation method according to claim 6, characterized in that: The tablet press has a pressure of 150 MPa to 200 MPa, and a pressure holding time of 5 min to 10 min.

8. The preparation method according to claim 6, characterized in that: The pressure of the cold isostatic press is 200 MPa to 300 MPa, and the holding time is 5 min to 10 min.

9. The preparation method according to claim 1, characterized in that: The blank is sintered in a hydrogen atmosphere to obtain a heterogeneous molybdenum alloy, comprising: The billet is sintered at 1300° C. to 1600° C. in a hydrogen atmosphere for 1 h to 4 h to obtain a molybdenum alloy with a heterogeneous structure.

10. A heterogeneous molybdenum alloy, characterized in that: The heterogeneous structure molybdenum alloy is prepared by the preparation method of any one of claims 1 to 9.